Genetic structure and gene flow in the Flame Robin (Petroica phoenicea). (3rd April 2021) - Beckmann, Christa; Major, Richard E.; Frankham, Greta J.; Thomas, Shina; Biro, Peter A.; Ujvari, Beata; Neaves, Linda
ABSTRACT: Robins in the family Petroicidae are characteristic of the woodland bird community that is threatened in Australia as a result of habitat loss and fragmentation. Flame Robin ( Petroica phoenicea ) populations declined by 56% between 1980 and 2000, with habitat loss likely being the primary cause. Given that Flame Robins primarily breed at high elevation, populations may become more isolated due to anthropogenic change, resulting in increased inbreeding and loss of genetic diversity that may accelerate local extinction. We estimated the genetic structure and recent gene flow among four populations (n = 70 birds) of this vulnerable (NSWSC) species across a 670 km portion of its range in temperate south-eastern Australia using 14 genetic markers. We found no significant differences in genetic diversity amongst populations and little population structuring – only the northernmost population showing a weak signal of differentiation. However, we detected little recent migration between the northern and southern sites, possibly due to recent fragmentation. We conclude that habitat loss is a conservation concern for this Vulnerable species and further work and ongoing genetic monitoring is needed, particularly given high elevation breeding sites that are vulnerable in the face of a changing climate.